2019
DOI: 10.3390/antiox9010019
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Polyphenolic Plant Extracts

Abstract: Plant polyphenols are secondary metabolites characterized by one or more hydroxyl groups binding to one or more aromatic rings [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
94
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(99 citation statements)
references
References 43 publications
4
94
0
1
Order By: Relevance
“…The presence of grape stems during fermentation increases the wine astringency, mainly due to its high content of proanthocyanidins [ 27 ]. Grape stems have a high content in phenolic compounds, biomolecules with strong antioxidant activity that can effectively act as radical scavengers [ 28 ]. Phenolic acids, flavan-3-ols, flavonoids, and stilbenes are the main polyphenols in grape stems [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of grape stems during fermentation increases the wine astringency, mainly due to its high content of proanthocyanidins [ 27 ]. Grape stems have a high content in phenolic compounds, biomolecules with strong antioxidant activity that can effectively act as radical scavengers [ 28 ]. Phenolic acids, flavan-3-ols, flavonoids, and stilbenes are the main polyphenols in grape stems [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, cereal grains such as rice have attracted much scientific attention [1] because they contain phenolic compounds such as quercetin, ferulic acid, and salicylic acid [2] which have strong antioxidant abilities [3]. Over the years, oxidative stress has been shown to play a key role in the pathogenesis of hypertension [4,5] since reactive oxygen species can cause endothelial dysfunction [6] leading to arterial stiffness in humans [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The polyphenols contained in areca nut have carcinogenic and anti-carcinogenic effects. For example, some reports indicate that the beneficial effects of polyphenols include antioxidant capacity to prevent damage caused by oxidative stress [47] as well as their biological effects through chromatin remodeling and other epigenetic modifications [48][49][50]. On the contrary, a series of studies have shown that polyphenols are another potential active carcinogen because they produce ROS (e.g., HO) and further form 8-OH-dG when mixed with lime to form oral environment alkalines (pH ≥ 9.5) which subsequently destroys DNA [44,51,52].…”
Section: Betel Quidmentioning
confidence: 99%